Involvement of CmWRKY10 in Drought Tolerance of Chrysanthemum through the ABA-Signaling Pathway - Jaffar, Muhammad Abuzar (Int J Mol Sci, 2016)
Drought is one of the important abiotic factors that adversely affects plant growth and production. The WRKY transcription factor plays a pivotal role in plant growth and development, as well as in the elevation of many abiotic stresses. Among three major groups of the WRKY family, the group IIe WRKY has been the least studied in floral crops. Here, we report functional aspects of group IIe WRKY member, i.e., CmWRKY10 in chrysanthemum involved in drought tolerance. The transactivation assay showed that CmWRKY10 had transcriptional activity in yeast cells and subcellular localization demonstrated that it was localized in nucleus. Our previous study showed that CmWRKY10 could be induced by drought in chrysanthemum. Moreover, the overexpression of CmWRKY10 in transgenic chrysanthemum plants improved tolerance to drought stress compared to wild-type (WT). High expression of DREB1A, DREB2A, CuZnSOD, NCED3A, and NCED3B transcripts in overexpressed plants provided strong evidence that drought tolerance mechanism was associated with abscisic acid (ABA) pathway. In addition, lower accumulation of reactive oxygen species (ROS) and higher enzymatic activity of peroxidase, superoxide dismutase and catalase in CmWRKY10 overexpressed lines than that of WT demonstrates its role in drought tolerance. Together, these findings reveal that CmWRKY10 works as a positive regulator in drought stress by regulating stress-related genes.